Not so plain as black and white : Afro-German culture and history, 1890-2000 - Mazón, Patricia M.; Steingröver, Reinhild; Berman, Russell A., 1950- (Rochester studies in African history and the diaspora, 2005)
"After World War II, "brown babies" were born to African American GIs stationed in Germany and German mothers." "Today there are 500,000 Afro-Germans in Germany out of a population of 80 million. Nevertheless, German society still sees them as "foreigners," assuming they are either African or African American but never German." "As editors Patricia Mazon and Reinhild Steingrover argue, the experience of Afro-Germans provides insight into contemporary Germany's transformation, willing or not, into a multicultural society. Furthermore, looking at Afro-Germans allows us to see another dimension of the ideas of race that shaped the twentieth century and led to the Holocaust."--Jacket